Non-financial value-added of venture capital: A comparative study of different venture capital investors - Terttu Luukkonen; Mari Maunula (The Research Institute of the Finnish Economy (ETLA), 2007)
This study focuses on the non-financial value-added Venture Capital (VC) investors bring to their portfolio companies, especially when these represent early-stage, high-technology and high-growth companies. The study draws attention to the extent and nature of non-financial value-added and analyses whether and in what ways different types of VC investors differ in this respect. The data were collected via a web-based survey tool in the autumn of 2006. The study takes into consideration the viewpoint of VC investors as it focuses on Finnish VC companies (private sector VCs), public sector VC organisations and informal investors (business angels). An effort was made to collect data from foreign investors active in Finland though they did not respond actively. Major findings of the study included the observation that private sector VCs were the most and public sector VCs the least active in monitoring their portfolio companies. Informal VCs were less active than expected. The different investor types had distinct profiles in providing management support and advice. Overall, private sector VCs evaluated the non-financial support they provided as the most and public sector VCs the least important for the success of their portfolio companies while informal VCs were between these extremes. These findings differed from those obtained in our study on the value-adding function of VCs in biotechnology, according to which informal VCs were found to have the highest overall value-added and kept closest contacts with their investee firms.
Keywords: O16; G24; G32; 330; venture; capital; Investition; Risikokapital; Unternehmensberatung; Betriebliche Wertschöpfung; Finnland